1993
DOI: 10.1080/08886504.1993.10782091
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Evaluating Measures of Computer Ability

Abstract: Most researchers and educators evaluating computer ability or literacy have used a construct approach. A prototypical measure assesses programming ability, application software skill, and computer awareness. This kind of measure is often viewed as a final product rather than as a pedagogical tool. In this article, it is argued that the fundamental basis of computer ability measures should be altered in order to address a rapidly evolving computer software market and take advantage of significant advances made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In 1992, Kay reviewed 36 studies on gender and computer related behaviors. While there were clear measurement concerns regarding the assessment of gender differences in computer ability, attitude, and use (e.g., Kay, 1992Kay, , 1993Kay, , 1994, the overall picture indicated that males had more positive attitudes, higher ability, and used computers more. Five years later, a meta-analysis by Whitley (1997) revealed that the imbalance between males and females continued to exist with respect to computer attitudes.…”
Section: Gender Differences and Computersmentioning
confidence: 99%
“…In 1992, Kay reviewed 36 studies on gender and computer related behaviors. While there were clear measurement concerns regarding the assessment of gender differences in computer ability, attitude, and use (e.g., Kay, 1992Kay, , 1993Kay, , 1994, the overall picture indicated that males had more positive attitudes, higher ability, and used computers more. Five years later, a meta-analysis by Whitley (1997) revealed that the imbalance between males and females continued to exist with respect to computer attitudes.…”
Section: Gender Differences and Computersmentioning
confidence: 99%